2001
DOI: 10.1108/13522750110393044
|View full text |Cite
|
Sign up to set email alerts
|

A new research medium, new research populations and seven deadly sins for Internet researchers

Abstract: The increasing use of Internet-based qualitative and quantitative research is based on both``pull'' and``push'' factors.``Pull'' factors include research clients' demand for faster turnaround and low cost, while marketing research agencies' naturally competitive endeavours represent thè`p ush''. Attempts``to clear the e-mist'' regarding research on the Internet and examines the main types of Internet based research (qualitative and quantitative) as well as seven``sins'' for Internet researchers ± based on inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 4 publications
(3 reference statements)
1
25
0
Order By: Relevance
“…Eaton and Struthers (2002), in a survey of workplace attitudes, found that the e-survey responses were fuller and more incisive than responses from postal questionnaires and this was the gain that was being sought in the current evaluation. This accords with the views of Eamon (2001) and Nancarrow et al (2001), who point to the possibility of online respondents having a greater opportunity to interpret e-questions in their own way. Whilst this might present problems for analysis, the possibility of responses being grounded in experience is enhanced through the use of online survey approaches.…”
Section: The Target Groupsupporting
confidence: 88%
See 2 more Smart Citations
“…Eaton and Struthers (2002), in a survey of workplace attitudes, found that the e-survey responses were fuller and more incisive than responses from postal questionnaires and this was the gain that was being sought in the current evaluation. This accords with the views of Eamon (2001) and Nancarrow et al (2001), who point to the possibility of online respondents having a greater opportunity to interpret e-questions in their own way. Whilst this might present problems for analysis, the possibility of responses being grounded in experience is enhanced through the use of online survey approaches.…”
Section: The Target Groupsupporting
confidence: 88%
“…Above all it does not prescribe what the evidence will be-rather it provides an opportunity for conclusions to grow from the evidence, a truly grounded approach. When comparing its use in educational research with that in marketing and medical research as outlined by Moss and Hendry (2002), Nancarrow et al (2001) and Illingworth (2001)-all of which used instruments that were more objective in content, the esurvey shows the capacity of the approach to elicit more subjective and reflective responses with comparable efficiency.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…6 Clearly, the potential for research participants is well beyond that which could be reached with traditional survey methods. This increased pool of participants has many positive implications for organizational researchers.…”
Section: Potential Benefits To Organizational Researchersmentioning
confidence: 99%
“…5,9 Although most Internet users are in North America, there are an estimated 69 million people with Internet access in Asia/ Pacific and 83 million in Europe. 6 Finally, it is also easier to reach more specialized populations such as those working in particular industries or job positions, gays/ lesbians/bisexuals, and people with physical disabilities or medical conditions. 4,10,11 If a researcher was interested, for example, in how people with physical disabilities cope with workplace stress, posting a message to a newsgroup for people with disabilities could reach more potential participants than soliciting them directly from specific organizations.…”
Section: Potential Benefits To Organizational Researchersmentioning
confidence: 99%